Fundamentals of computer graphics - Marschner, Steve; Shirley, Peter (CRC Press/Taylor and Francis Group, 2022)
"The fifth edition of Fundamentals of Computer Graphics continues to provide an outstanding and comprehensive introduction to basic computer graphic technology and theory. It retains an informal and intuitive style while improving precision, consistency, and completeness of material, allowing aspiring and experienced graphics programmers to better understand and apply foundational principles to the development of efficient code in animation, visual effects, games, visualization, advertising, and other applications"--